Elucidation of acid strength effect on ibuprofen adsorption and release by aluminated mesoporous silica nanoparticles1. Issue 38 (30th April 2015) - Kamarudin, N. H. N.; Jalil, A. A.; Triwahyono, S.; Sazegar, M. R.; Hamdan, S.; Baba, S.; Ahmad, A.
<x xml:space="preserve">Abstract</x> Mesoporous silica nanoparticles (MSN) with 1–10 wt% loading of aluminum (Al) were prepared and characterized by XRD, N2 physisorption, 29Si and 27Al NMR, FT-IR and FT-IR preadsorbed pyridine.